Evolution of occlusal pathology. A literature review. - Camilo Guerrero; Dairo Marín; Ángela Galvis (Universidad de Concepción., 2013)
Introduction: Many of the guidelines on occlusion and treatment alternatives in dentate and partially edentulous patients, are based on concepts raised in the beginning of dentistry. The diversity of the occlusion schools has become some of these concepts complex to understand and apply. This diversity makes difficult the compression of the occlusal physiology and its disorders, hindering the understanding of the occlusal pathology and its proper diagnosis and management. Objective: This is why we conducted a literature review about oclusal physiology and pathology, in order to gather information based on scientific evidence, which in order to clarify concepts and homogenize knowledge about physiological and morphological changesof thestomatognathic system, associated toocclusal alterations, allowing the future standardization of the occlusal diagnostic process at the Faculty of Dentistry of the National University of Colombia. Methodology: A search was conducted inMedLine, PubMed, Ovid, Ebsco, ScienceDirect and Hinari-Healthinternetwork using the Mesh terms: "Dental Occlusion" - "Stomatognathic System" - "masticatory System" - Temporomandibular Joint and the bibliographies of papers and review articles that had direct relationship to the topic; the publication deadline was not taken into account. In total, 79 articles, 10 texts and 7 websites were obtained. Conclusion: Occlusal pathology is an evolutionary process that might affect the form and/or function of any of the components of the stomatognathic system. Occlusal Harmony is a state in which each part of the system works in concert with the others to fulfill the functions of mastication, speech and swallowing; oral rehabilitation should be directed toward obtaining a harmonious occlusion.